Answer:
![y=-(1)/(3) (x-5)^2+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/rn1gac3deljqh78xw83q586vnquk2lzn8u.png)
Explanation:
We are given the following;
- Vertex of a quadratic function = (5,3)
- A point where the function passes through (-1, -9)
Required to determine the equation of the function;
- We need to know the vertex form of a quadratic function is;
, where h and k correspond to the vertex (h,k)
- Therefore, we can replace the variables h and k of the vertex in the equation;
That is;
![y=a(x-5)^2+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ouynwnhprg40w41q1hw2lh2okvt2s4i1yg.png)
Then we use the equation and the point given to solve for a
x = -1 and y = -9
We get;
![-9=a(-1-5)^2+3\\-9 = a(36) + 3\\-9 - 3 = 36a\\-12 =36a \\a=-(1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/uelxovp1mf80ylt7k2mq5qytlss6vnew3p.png)
Substituting the values of a, h and k in the equation, we get;
![y=-(1)/(3) (x-5)^2+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/rn1gac3deljqh78xw83q586vnquk2lzn8u.png)
Thus, the equation of the function in the vertex form is
![y=-(1)/(3) (x-5)^2+3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/rn1gac3deljqh78xw83q586vnquk2lzn8u.png)